PEMODELAN MATEMATIKA PENYEBARAN POLUTAN UDARA DI KAWASAN PLTU MENGGUNAKAN METODE VOLUME HINGGA - Masyhudi, Muhammad Ali; Fatahillah, Arif; Setiawan, Toto Bara (Kadikma, 2018)
The existence of a Steam Power Plant greatly helps human electricity needs.The other side, the existence of the power plant activity has a negative impact on the environment. The use of coal fuel produces an air pollutant. The spread of air pollutants is influenced by interrelated variables. The existence of mathematical modeling as an applied science helps represent a problem from real world situations into mathematical language to find solutions to these problems. Mathematical modeling helps build a mathematical formula that describes the spread of air pollutants with actual conditions without ignoring important factors in the system. The analytical exact solution to the problem of spreading air pollutants is very difficult. Therefore, a numerical method approach is used in the form of a volume up method. In this research a mathematical model was built on the distribution of air pollutants based on momentum and mass quantity equations. Keywords: Mathematical Modeling, Air Pollutants, Finite Volume Method